Intraspecific variation in Typhlocharis Dieck, 1869 (Coleoptera, Carabidae, Anillini): the case of two new species of the baetica group - Pérez-González, Sergio; Zaballos, Juan P.; Ghannem, Samir (Zootaxa, 2013)
Two new species of Typhlocharis Dieck, 1869 from the southwest of the Iberian Peninsula included in baetica species group are described: T. acutangula n. sp. and T. mixta n. sp. The new species can be easily recognized by the presence of an anterodistal dentiform projection in metatibia (T. acutangula sp.n) and pseudotetramery and a medial tooth in clypeus (T. mixta sp.n), features not observed in any other species of the group, but present in quadridentata and gomezi groups respectively. An updated key of baetica group is provided. The large series of T. mixta n. sp. allowed a good study of intraspecific variation, which is detailed and compared within the genus. Implications for the systematics and relations of the baetica group are discussed. Intraspecific variations are grouped in four categories: individual variations in shape, size and proportions, alterations in chaetotaxy, asymmetries, and teratologies or malformations. Finally, implications and problems of intraspecific variability for the systematics of the genus are discussed.